2023
DOI: 10.3389/fimmu.2023.1089001
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting matrix metalloproteases in diabetic wound healing

Abstract: Chronic inflammation participates in the progression of multiple chronic diseases, including obesity, diabetes mellitus (DM), and DM related complications. Diabetic ulcer, characterized by chronic wounds that are recalcitrant to healing, is a serious complication of DM tremendously affecting the quality of life of patients and imposing a costly medical burden on society. Matrix metalloproteases (MMPs) are a family of zinc endopeptidases with the capacity of degrading all the components of the extracellular mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 108 publications
(79 reference statements)
0
32
0
Order By: Relevance
“…[ 35 ] ROS can enhance the stress state of functional cells, resulting in increased activity of signaling pathways secreting pro‐inflammatory cytokines, chemokines, and MMPs in damaged tissues, which are closely associated with difficult‐to‐heal wounds. [ 36 ] Therefore, ROS generation and clearance are necessary conditions to ensure the effectiveness and timeliness of wound healing.…”
Section: Ros Homeostasis and Relevance Of Ros In Diabetic Woundsmentioning
confidence: 99%
“…[ 35 ] ROS can enhance the stress state of functional cells, resulting in increased activity of signaling pathways secreting pro‐inflammatory cytokines, chemokines, and MMPs in damaged tissues, which are closely associated with difficult‐to‐heal wounds. [ 36 ] Therefore, ROS generation and clearance are necessary conditions to ensure the effectiveness and timeliness of wound healing.…”
Section: Ros Homeostasis and Relevance Of Ros In Diabetic Woundsmentioning
confidence: 99%
“…Recently, drugs derived from food to treat many diseases are gaining acceptance (Chen, Qin, et al, 2023; Chen, Zhong, et al, 2023). Flavonoids, as a bunch of polyphenolic compounds made in plants as secondary metabolites, are extensively exist in fruits, vegetables, and herbs, which have a wide range of biological activities (Chen et al, 2022).…”
Section: Discussion and Further Perspectivementioning
confidence: 99%
“…Diabetes mellitus (DM), featured by persistent hyperglycemia, is a chronic metabolic noncommunicable disease that may impact over 783 million people globally by 2045 (Chen, Qin, et al, 2023). Although the exact pathogenesis is not fully elucidated, studies have shown that suppression of α‐glucosidase and non‐enzymatic glycation has been shown to be an effective approach to treat T2DM (Hossain et al, 2020).…”
Section: Promising Role Of Galangin In Various Diseasesmentioning
confidence: 99%
“…[7][8][9] Besides, continuous hyperglycemia in diabetic patients not only leads to impaired immune response but also provides nutrition for bacteria, resulting in diabetic wounds being more vulnerable to bacterial infection. 10 Persistent bacterial infection of diabetic wounds is one of the main causes of impaired wound healing. In response to this feature, topical antibiotics are usually used clinically to control bacterial infection.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] In addition to immunosuppression persistent high levels of glucose can lead to neurological, microvascular, and macrovascular lesions, which makes diabetic wounds difficult to heal. 10 Therefore, to accelerate the healing of diabetic wounds, we usually need to control blood glucose levels. In general, diabetics can control their blood glucose levels by injecting insulin.…”
Section: Introductionmentioning
confidence: 99%